Prevalensi dan Intensitas Ektoparasit Ika Nila (Oreochromis niloticus) di Bendungan Telaga Tunjung, Tabanan - Ida Ayu Grisandi Dewi Kurnia; Pande Gde Sasmita Julyantoro; Endang Wulandari Suryaningtyas (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2019)
This study aims to determine the value of the prevalence and intensity of ectoparasites in Tilapia (Oreochromis niloticus) in Telaga Tunjung Dam and measure the parameters of water quality, temperature, pH, and DO. The number of tilapia studied was 30, sampling was done at 3 stations in Telaga Tunjung Dam. Identification of ectoparasites was carried out at the Fisheries Science Laboratory, Water Resources Management Study Program, Faculty of Marine and Fisheries, Udayana University. Ectoparasites were identified in the mucus, dorsal, caudal, operculum and gill organs of the tilapia by skin scraping and wet mount methods. Data were analyzed by descriptive quantitative which calculated differences in the prevalence and intensity of ectoprasite infections and correlation tests to determine the relationship of length and weight of fish with intensity. The results of the three stations show the prevalence value with the